USING TRADITIONAL NATIONAL DECORATIVE ELEMENTS IN MODERN GARMENTS - Мельник, Л. М.; Конотоп, А. С.; Кизимчук, О. П. (Art and Design, 2018)
The purpose of this work is to establish the possibility of the decorating of modern women’s clothes with artistic elements and ornaments of traditional national clothes of Ukraine different regions and their subsequent reproduction in knitwear. Methods of literary-analytical review and visual-analytical research are used.The elements of clothing decoration that are characteristic of ethnic Ukrainian clothing have been defined during the research. The structures of knitted fabrics based on on openwork, plated and interlooping with unrolling, which simulate different merezhka of traditional Ukrainian embroidery, have been developed in this study. The few variants of simple mesh are offered: narrow one made on the basis of the rib 1 + 1 with an unrolling; narrow complex canvas - on the basis of openwork interlooping; wide (more than 2 cm) canvas - on the basis of a plated interlooping. The model of the women’s dress is executed in the semi-regular way on two-bar flat-knitted machine, using the developed variants of knitted fabric structures. Taking into account the traditions of an arrangement of the embroidery decoration elements and modern fashion trends, it is proposed to use a narrow simple snap-net to decorate the neck of the product, a wide snap-net, having a plant ornament to knit 2/3 of the bottom of the sleeve. The narrow canvas is also used as a connecting element of the sleeve parts made with various interlooping. The decoration elements of national Ukrainian clothes have been investigated and reproduced in women’s knitted dress by new knitted structure creation taking into account modern technology. Research results can be used to expand the range of modern women’s clothing